Diagnostik und Therapie akuter Erkrankungen der thorakalen Aorta - Schotten, Sebastian; Pitton, Michael B. (Radiologie up2date, 2017)
Akute Erkrankungen der thorakalen Aorta sind zwar eher selten, aber lebensbedrohlich. Sie erfordern daher eine rasche Diagnostik und Therapie. Diagnostisch spielt dabei die CT-Angiografie die zentrale Rolle, therapeutisch stehen der offene Ersatz bei der Aorta ascendens und die endovaskulären Therapieverfahren bei der Aorta descendens an erster Stelle.Acute diseases of the thoracic aorta represent a relatively rare but life threatening spectrum of pathologies. The non-traumatic diseases are usually summarized by the term “acute aortic syndrome”. A timely diagnosis and initiation of therapy are cornerstones for the patient outcome. CT has become the standard imaging procedure due do its widespread availability and excellent sensitivity. Furthermore, CT is able to discriminate the variants of acute aortic diseases and to detect the wide spectrum of complications. The volumetric CT dataset is also the basis for planning of interventional procedures. Open surgical repair still represents the standard of care for acute pathologies of the ascending aorta while endovascular therapy, due to minimally invasive character and good outcome, has replaced open surgery in most cases of complicated lesions of the descending aorta.
Keywords: Aorta; akutes Aortensyndrom; endovaskuläre Behandlung